Establishment of a Framework to Support Multi-Faceted Initiatives for Pharmacy-Practice Transformation: Lessons Learned - Renee Robinson; Shanna K. O'Connor; Hayli Hruza; Elaine Nguyen; Michael A. Biddle; Angela Jaglowicz; Thomas G. Wadsworth (MDPI AG, 2021)
We describe the first two years of a multifaceted, five-year program to support sustainable pharmacist-provided health services in Alaska. In 2018, the Alaska Pharmacists Association funded the Sustainable Education and Training Model under Pharmacist as Providers (SETMuPP) to train and support pharmacists to navigate the insurance medical billing process for nondispensing healthcare services. The SETMuPP employed a three-pillar implementation approach: (1) training and practice support infrastructure, (2) PharmD curriculum augmentation, and (3) advocacy and legislative support. The first two years have demonstrated the effectiveness of triad partnerships between professional associations, state policy makers, and academic centers to catalyze meaningful practice transformation.